2019
DOI: 10.1007/s00109-019-01781-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic signature of type 1 diabetes-induced sensory loss and nerve damage in diabetic neuropathy

Abstract: Objective: Diabetic-induced peripheral neuropathy (DPN) is a highly complex and frequent diabetic late complication, which is manifested by prolonged hyperglycemia. However, the molecular mechanisms underlying the pathophysiology of nerve damage and sensory loss remain largely unclear. Recently, alteration in metabolic flux have gained attention a basis for organ damage in diabetes; however, peripheral sensory neurons have not been adequately analyzed with respect to metabolic dysfunction. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 28 publications
4
29
1
2
Order By: Relevance
“…43 The abundance of L-malic acid was signicantly reduced in liver of the diabetic rats 44 and in peripheral nerves of type I diabetes. 45 The fecal abundance of L-malic acid was signicantly reduced in GDM women in this study, suggesting an opposite effect of fecal metabolites on hyperglycemia.…”
Section: Discussionmentioning
confidence: 51%
“…43 The abundance of L-malic acid was signicantly reduced in liver of the diabetic rats 44 and in peripheral nerves of type I diabetes. 45 The fecal abundance of L-malic acid was signicantly reduced in GDM women in this study, suggesting an opposite effect of fecal metabolites on hyperglycemia.…”
Section: Discussionmentioning
confidence: 51%
“…In our study, pathway analysis highlighted the TCA cycle in diabetic rats (Supplementary Figure S4). The abnormality of TCA cycle was also described in urine and sciatic nerve of STZ-induced diabetic mice (You et al, 2016;Rojas et al, 2019). From another integrated proteomics and metabolomics study (Freeman et al, 2016), six enzymes in TCA cycle were significantly increased in the sciatic nerves of diabetic rats.…”
Section: Metabolic Pathway Analysis and Biological Function Of The Idmentioning
confidence: 90%
“…These results indicated that the mechanism of JMT decoction relieving DPN was closely associated with the regulation of abnormal lipid metabolism. Tricarboxylic acid (TCA) cycle, the main pathway of carbohydrate metabolism in mitochondria, was reported to be impaired in diabetes and its complications (Filla and Edwards, 2016;Wu et al, 2017;Mathew et al, 2019;Rojas et al, 2019). TCA cycle that is also related to mitochondrial function plays a central role in maintaining peripheral nervous function and structure.…”
Section: Metabolic Pathway Analysis and Biological Function Of The Idmentioning
confidence: 99%
See 2 more Smart Citations